A borane laser - Cerdán, Luis; Braborec, Jakub; Garcia-Moreno, Inmaculada; Costela, Angel; Londesborough, Michael G S (Nature communications, 2015)
Emission from electronically excited species forms the basis for an important class of light sources-lasers. So far, commercially available solution-processed blue-emitting laser materials are based on organic compounds or semiconductor nanocrystals that have significant limitations: either low solubility, low chemical- and/or photo-stability and/or uncompetitive prices. Here we report a novel and competitive alternative to these existing laser materials that is based on boron hydrides, inorganic cluster compounds with a rich and diverse chemistry. We demonstrate that solutions of the borane anti-B18H22 show, under pulsed excitation, blue laser emission at 406 nm with an efficiency (ratio of output/input energies) of 9.5%, and a photostability superior to many of the commercially available state-of-the-art blue laser dyes. This demonstration opens the doors for the development of a whole new class of laser materials based on a previously untapped resource for laser technology-the boranes.